Рятівні дослідження поселення Хрінники 8 у 2008 р. - Козак, Д.Н.; Ткач, В.В. (Археологічні дослідження в Україні, 2009)
The main achievements of the research of a new site at the Khrinnyky reservoir are briefly described in the paper. The materials of several Bronze Age burials are unique.